ANALISIS KINERJA KEUANGAN PERUSAHAAN YANG TERMASUK DALAM KELOMPOK INDEKS LQ 45 DAN JII DENGAN MENGGUNAKAN ROE DAN ROA PADA BURSA EFEK INDONESIA TAHUN 2010 - Nasution, Yan Noviar; Herdiyana, Herdiyana (Universitas Pakuan, 2011)
This Research is entitled “The Analysis of the Financial Performance Companies which Included in group an index to LQ 45 And JII by using ROE and ROA at Indonesia Stock Exchange in the Year of 2010”. As for target of this research to know the difference between the mean of Return Equity on ( ROE) and Return On Assets ( ROA) of the public companies is merged into go to group of LQ 45 which have large asset and LQ 45 which have small asset, of the public companies is merged into go to group of JII which have large asset and JII which have small asset, and of the public companies is merged into go to group of LQ 45 which have large asset and JII which have large asset and also of the public companies is merged into go to group of LQ 45 which have small asset and JII which have small asset and of the public companies is merged into go to group of LQ 45 which have large asset and JII which have small asset and also of the public companies is merged into go to group of LQ 45 which have small asset and JII which have large asset .The research method used is case study of the public companies which is merged into go to group of LQ 45 and JII ( Jakarta Islamic Index ) which are listed in Indonesia Stock Exchange. Analysis of the different test using the criteria of asset ownership, meaning the companies split in two groups of assets, the company went public that beraset beraset small and large. Where restrictions on the size of a company, obtained from the calculation of the average assets held by the sample firms went public in each group of assets While companies taken as sample is companies which enlist in two period of the announcement of Indonesia Stock Exchange or one full year of (2010) and data used in this research is data of secondary in Web IDX.Based on the hypothesis test results concluded that there are significant differences between the ROA average of the public companies is merged into go to group of LQ 45 which have large asset with the average ROA of the public companies is merged into go to group of JII which have large asset or which have small asset. As well as that there are significant difference between the average the ROA of the public companies is merged into go to group of JII which have large asset with the average the ROA of the public companies is merged into go to group of JII which have small asset. While for the group of LQ45 index there is no significant difference between the ROA average of the public companies is merged into go to group of LQ 45 which have large asset with the ROA average of the public companies is merged into go to group of LQ 45 which have small asset. Meanwhile, for the ROE average in general there is no significant difference between of the public companies is merged into go to group of LQ 45 or the group of JII, except between the ROE average of the public companies is merged into go to group of LQ 45 which have large asset with the average ROE of the public companies is merged into go to group of JII which have large asset.